Analisis Kualitas Rotogravure pada Bagian Printing dengan Menggunakan Metode Failure Mode and Effect Analysis dan Fault Tree Analysis di PT. Diantrijaya Mukti Utama - Adham Roihan Azriel Irfani; Rochmoeljati Rochmoeljati (Pusat Riset dan Inovasi Nasional, 2023)
One company that produces rotogravure products is PT. Diantrijaya Mukti Utama. The company implements a make to order production system. In this research, problems were found in the rotogravure production section. Namely in the form of damage to the printing machine with the average age of the machine being still young but often causing defects. The aim of this research is to identify potential failures on printing machines, find out the root causes of their occurrence on printing machines using the fault tree analysis method and produce alternative recommendations for improvement using the Failure Mode and Effect Analysis method in the printing process at PT Diantrijaya Mukti Utama. The research results showed that there were 3 types of defects in the PT printing process. Diantrijaya Mukti Utama, namely hazing defects, streaks and ink fading with a chance of defects occurring of 0.03%, 0.005%, 0.013%. Of these three defects, the causes of defects include workers being less skilled in setting the doctor blade, the doctor blade being used being damaged. Recommended improvements are to provide training related to the use of doctor blades to workers so they can know how to use and care for the doctor blades used